Integrating the RADEC Model in Differentiated Learning to Enhance Reflective Thinking: A Case Study in Indonesian Elementary Education - Intan Budi Komara; Faisal Sadam Murron; Wahyu Sopandi (Universitas Pendidikan Ganesha, 2025)
The increasing diversity of learning styles, interests, and readiness among elementary school students requires more than just generic teaching; it necessitates an adaptive, reflective, and inclusive pedagogical framework. This study aims to explore the integration of the RADEC (Read, Answer, Discuss, Explain, Create) model in a differentiated learning approach to improve students' reflective thinking skills. The research method used is descriptive qualitative with a single case study design. Data were collected through participatory observation, in-depth interviews, and document analysis. Data analysis was conducted using a thematic approach to identify the main patterns that emerged during the learning process, with a focus on adapting the RADEC model to the different learning needs of students. The results showed that each stage of RADEC was meaningfully adapted to the students' learning profiles through variations in content, learning processes, and work outcomes. Students showed significant development in metacognitive behaviors, such as self-assessment skills, critical questioning, and contextualization of knowledge. Despite limited resources and time, the success of the implementation was supported by teacher collaboration and parental involvement. This research contributes to the strengthening of reflective pedagogy by presenting RADEC-based differentiation as a contextual innovation that is feasible to implement and in line with the spirit of the Merdeka Curriculum.of reflective pedagogy by presenting RADEC-based differentiation as a contextual innovation that is feasible to implement and in line with the spirit of the Merdeka Curriculum.